EVIDENCE-BASED PRACTICE: INCLUSIVE EDUCATION FOR THE EFFECTIVE IMPLEMENTATION FOR CHILDREN WITH AUTISM (Proceedings of the International Conference on Education, 2017)
Interventions for autism are increasing being held to standards such as ‗evidence-based practice‘ in psychology and ‗scientifically-based re-search‘ in education. At the factor when these ideas rose with regards to psychotherapy and regular education, they brought on substantial debate. Evidence-based practices (EBPs) are the premise on which educators and other specialist coops are required to outline educational programs for students with autism spectrum disorders (ASD). Inclusive education as a late modernity reform project is exemplified in the call for ‗Education for All‘. Despite the simplicity of its message, inclusion is highly debatable. General education teachers have differing views about the inclusion of students with ASD in mainstream class-rooms. However, the type and severity of the Autistic children‘s affect teachers‘ willingness to accommodate certain students and their confidence that they will effectively manage their classrooms. The Implementation science guides the movement of innovations, such as transforming evidence-based practices for students with ASD into regular practices at school. This article is presented as an inclusive educational model to build systems of professional development that increase the quality of services and promote teachers' use of evidence-based practices. Further, it is proposed that the ASD community align with the greater inclusive education reform movement.
Keywords: Inclusive education; Autism Spectrum Disorder; Effective Implementation; Evidencebased practice (EBP)